Implementation of Bang-Bang Charge Control for an LLC Resonant Converter for Battery Charger - Potjanatkomol, Natkamol; Polmai, Sompob; Wiangtong, Theerayod (My University, 2025)
This paper presents the design of a 2-kW full-bridge LLC resonant converter for battery charger operating in a range of DC input voltages of 380-420 V and output voltage of 60 V. The bang-bang charge control technique, whose controller adjusts the threshold voltage of the bang-bang comparators, is adopted for controlling the converter switching frequency. This control method provides fast single-pole control-to-output transfer function resulting in simplicity of controller design. In this paper the design procedure of LLC converter resonant circuit is presented and a prototype is built. The discrete-time PI compensator for constant voltage (CV) and constant current (CC) control is implemented using STM32 microcontroller. The simulation and experimental results show satisfactory control characteristics.
Keywords: bang-bang charge control; battery charger; LLC resonant converter